Exploring Banking Reforms in Nigeria: Economic Impacts and Future Implications - Muhammad, Auwalu Shuaibu; Fitrianto, Achmad Room (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
In the growing global economy, establishing a robust banking sector has become an essential concern for governments worldwide. Nigeria, like many other nations, has witnessed successive governments implementing economic reforms to navigate the challenges of the global market. Given the indispensable role of the financial sector, particularly banking industry, numerous reforms have been legislated over the past three decades. This paper examines these banking reforms and their profound impacts on the Nigerian economy. The primary objective of this study is to consolidate and synthesize the findings of previous empirical research regarding banking reforms and their effects on Nigeria's economy, as measured by Gross Domestic Product (GDP). This paper employed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The analysis reveals that the banking reforms undertaken by successive Nigerian governments have significantly influenced the nation's economic growth. However, the persistent issue of high interest rates poses a deterrent to investors seeking loans and advances. Consequently, the study advocates for a strategic shift in lending practices within the real sector towards Islamic banks, where loans are structured based on profit and loss sharing rather than conventional interest-based mechanisms. Furthermore, the paper emphasizes the need for future banking reforms to address recurring inflationary pressures and foreign exchange market volatility in Nigeria.